Incidence of childhood cancer in Latin America and the Caribbean: coverage, patterns, and time trends - Neimar de Paula Silva; Murielle Colombet; Florencia Moreno; Friederike Erdmann; Anastasia Dolya; Marion Piñeros; Charles A Stiller; Eva Steliarova-Foucher; the IICC-3 contributors (Pan American Health Organization, 2024)
Objective. To provide a comprehensive overview of geographical patterns (2001-2010) and time trends (1993-2012) of cancer incidence in children aged 0-19 years in Latin America and the Caribbean (LAC) and interpret the findings in the context of global patterns. Methods. Geographical variations in 2001-2010 and incidence trends over 1993-2012 in the population of LAC younger than 20 years were described using the database of the third volume of the International Incidence of Childhood Cancer study containing comparable data. Age-specific incidence per million person-years (ASR) was calculated for population subgroups and age-standardized (WSR) using the world standard population. Results. Overall, 36 744 unique cases were included in this study. In 2001-2010 the overall WSR in age 0-14 years was 132.6. The most frequent were leukemia (WSR 48.7), central nervous system neoplasms (WSR 23.0), and lymphoma (WSR 16.6). The overall ASR in age group 15-19 years was 152.3 with lymphoma ranking first (ASR 30.2). Incidence was higher in males than in females, and higher in South America than in Central America and the Caribbean. Compared with global data LAC incidence was lower overall, except for leukemia and lymphoma at age 0-14 years and the other and unspecified tumors at any age. Overall incidence at age 0-19 years increased by 1.0% per year (95% CI [0.6, 1.3]) over 1993-2012. The included registries covered 16% of population aged 0-14 years and 10% of population aged 15-19 years. Conclusions. The observed patterns provide a baseline to assess the status and evolution of childhood cancer occurrence in the region. Extended and sustained support of cancer registration is required to improve representativeness and timeliness of data for childhood cancer control in LAC.